The disordered hypervariable region and the folded catalytic domain of oncogenic K-Ras4B partner in phospholipid binding. (February 2016) - Banerjee, Avik; Jang, Hyunbum; Nussinov, Ruth; Gaponenko, Vadim
Highlights: The C-terminal hypervariable region (HVR) of K-Ras4B is structurally disordered. We suggest that the K-Ras4B HVR can participate in auto-inhibition of K-Ras4B. The K-Ras4B HVR conformation may depend on the type of the bound nucleotide. The K-Ras4B HVR conformation may also depend on oncogenic mutations. Oncogenic mutations can shift the HVR-lipid binding selectivity. Abstract : The C-terminal hypervariable region (HVR) of the splice variant KRAS4B is disordered. Classically, the role of the post-translationally-modified HVR is to navigate Ras in the cell and to anchor it in localized plasma membrane regions. Here, we propose additional regulatory roles, including auto-inhibition by shielding the effector binding site in the GDP-bound state and release upon GTP binding and in the presence of certain oncogenic mutations. The released HVR can interact with calmodulin. We show that oncogenic mutations (G12V/G12D) modulate the HVR-phospholipid binding specificity, resulting in preferential interactions with phosphatidic acid. The shifts in the conformational preferences and binding specificity in the disordered state exemplify the critical role of the unstructured tail of K-Ras4B in cancer.